A nanowire-nanoparticle double composite polymer electrolyte for high performance ambient temperature solid-state lithium batteies. (10th October 2019) - Wang, Shi; Zhang, Lei; Li, Jingyu; Zeng, Qinghui; Liu, Xu; Chen, Pingping; Lai, Wen-Yong; Zhao, Tong; Zhang, Liaoyun
Abstract: Development of solid-state electrolytes that can allow corresponding lithium-ion batteries (LIBs) to perform excellent room temperature cell performance is very meaningful, and also is still a great challenge. One effective measure to solve the above problem is to reduce the interface resistance of the cells via special methods. In this study, a novel double composite polymer electrolyte using polyethylene oxide-polypropylene oxide-polyethylene oxide (PEO-PPO-PEO)/LiTFSI, ceramic nanowires and nanoparticles is designed and prepared (the composite electrolyte is named as CPE) for the first time, which combines the advantages of polymer electrolyte, ceramic nanowires and nanoparticles (different from the related works about only using ceramic nanopartices or ceramic nanowires as fillers). Compared with the composite electrolyte without adding ceramic nanoparticles (named as CPE-0), CPE presents higher ionic conductivity (4.58 × 10 −5 S cm −1 at ambient temperature), much higher lithium-ion transference number (0.28), which likely because nanoparticles can promote the formation of more continuous ion channels at the interface of polymer and ceramic fillers. In addition, the CPE shows much wider electrochemical window (5.6 V) than that of the CPE-0 (4.2 V), which can be attributed to the extra nanoparticles can further scavenge trace impurities. Especially, the galvanostatic cycling experiments confirm that CPE has much better stability against Li metal than that of CPE-0, while the Li/CPE/Li symmetric cell also shows a low and stable interface resistance of ∼800 Ω from day 1 to day 25. Therefore, the LiFePO4 /Li cell using the CPE shows good cycle performance at 28 °C. Specifically, the cell exhibits a discharge capacity of 154 mAh g −1 with coulombic efficiency of 100% at the 100 cycles. Our work indicates that the interface resistance of the corresponding batteries can be significantly reduced by preparation of CPE with specific polymer electrolytes and ceramic fillers. Thus, the solid-state cells can be well run at ambient temperature. Graphical abstract: Image 1 Highlights: A novel nanowire-nanoparticle double composite polymer electrolyte is prepared. This electrolyte has better electrochemical property than the single composite one. The assembled solid lithium-ion batteries show good cycle performance at 28 °C.